Older Adults and Substance-Related Disorders: Trends and Associated Costs. (24th April 2013) - Rosen, Daniel; Heberlein, Emily; Engel, Rafael J.
Abstract : Purpose . The aim of this study is to examine the changing service profile of older adults receiving substance abuse services over the past decade and the increased costs of treating this population. Design and Methods . Medicaid claims for mental health and substance abuse services data from a medium sized county in an eastern state were analyzed for individuals aged 50 years and older in calendar year 2000 or 2009. Univariate statistics are presented to describe the substance abuse and mental health services used by older adults in these two years. Results . The number of low-income older adults who accessed services for treatment and who had a substance-related diagnosis grew from 545 individuals in 2000 to 1, 653 individuals in 2009. Costs for services utilized by older adults with a substance-related diagnosis rose by 358% from $2.1 million in 2000 to $9.5 million in 2009. Implications . The increase in the number of low-income older adults with a substance-related disorder and the concomitant rise in total spending for Medicaid reimbursed services indicate that local and state social service providers need to prepare for an older adult population who will need appropriate substance abuse prevention and treatment programs.